Lumbar spinal stenosis exacerbated by spinal epidural lipomatosis: a case report - Fang, Yide; Bian, Zhenghang; Tong, Zhengyi; Xu, Jinhai; Mo, Wen (Frontiers in Surgery, 2026)
ObjectiveTo characterize the presentation, diagnostic strategy, and postoperative recovery patterns in a patient with lumbar spinal stenosis (LSS) complicated by spinal epidural lipomatosis (SEL), and to evaluate the role of selective nerve root block (SNRB) in guiding staged minimally invasive decompression.MethodsWe analyzed the clinical course of a 65-year-old man presenting with neurogenic claudication and right lower extremity numbness after a course of inhaled glucocorticoids. Preoperative assessment included radiography, computed tomography (CT), and magnetic resonance imaging (MRI), which demonstrated degenerative central canal stenosis at L4/5 and epidural lipomatosis at L5/S1. Because imaging findings were multilevel and symptom dominance was unclear, SNRB localized the symptomatic level and guided staged arthroscopy-assisted uniportal decompression. Clinical outcomes were assessed using the Visual Analog Scale (VAS), Oswestry Disability Index (ODI), SF-36 quality-of-life scores, walking tolerance, and neurological examinations during 4 months of follow-up.ResultsSNRB identified L4/5 as the primary symptomatic level, supporting initial targeted decompression. Following Stage 1 decompression at L4/5, neurogenic claudication and motor weakness improved rapidly, with VAS decreasing from 7 to 4 and ODI improving from 52 to 38. Persistent plantar numbness prompted Stage 2 decompression with excision of excessive epidural fat at L5/S1, after which VAS further decreased to 2 and ankle plantarflexion strength improved relative to baseline. At the final follow-up, ODI improved to 20 and the SF-36 composite score increased from 32.6 to 70.8. Walking tolerance markedly improved, only mild plantar paresthesia persisted. No perioperative complications or postoperative instability were observed.ConclusionsThis case suggests that SEL may trigger or unmask clinical symptoms of degenerative LSS and highlights distinct recovery trajectory between focal degenerative stenosis and diffuse epidural fat–related compression. SNRB-guided staged minimally invasive decompression enabled precise level selection and favorable functional outcomes, underscoring its value in managing multilevel lumbar pathology complicated by SEL.